Challenges and Strategies in Improving Numeracy for Grade V Students at SDN 4 Selat, Singaraja - Apriliawan, Kadek Erik; Yasa, I Nyoman Shindu; Putra, I Putu Agus Andika; Wulandari, Katarina Ni Made Sonia Putri; Arini, Ketut; Werang, Basilius Redan (Formosa Journal of Multidisciplinary Research, 2024)
This article aims to explore the challenges faced and the strategies implemented in improving the numeracy of class V students at SDN 4 Selat, Singaraja. With a qualitative approach, data is collected through in-depth interviews, classroom observations, and document analysis. The research results highlight several main challenges, such as limited educational resources, variations in student ability levels, lack of teacher training, non-conducive learning environments, and the digital divide. Strategies implemented to overcome these challenges include resource development, differential learning approaches, teacher training, improved learning environments, technology integration, and collaboration with parents. Thus, this research provides an in-depth understanding of the dynamics of numeracy at SDN 4 Selat and provides insight into the development of more effective mathematics education at the elementary school level.